E-government services evaluation from citizen satisfaction perspective: A case of Afghanistan. Issue 1 (21st March 2016) - Anwar, Mohammed; Esichaikul, Vatcharaporn; Rehman, Mariam; Anjum, Maria
Abstract : Purpose: – The purpose of this paper is to analyze and evaluate the current status of e-government services in Afghanistan. To identify the evaluation criteria based on citizen satisfaction from e-government services, the proposed government-to-citizen (G2C) evaluation model is considered in the context of Afghanistan. Design/methodology/approach: – A conceptual G2C evaluation model and e-government evaluation model are proposed. The criteria used for the G2C evaluation model is based on the demand and supply side, which have an immense effect on citizen satisfaction. The mixed research method (quantitative and qualitative) is used, and quantitative data analysis results are supported through qualitative data analysis. Findings: – The findings reveal that citizen satisfaction from e-government services in Afghanistan are affected by services availability on multiple channels, citizen-centric features, paralingual support, process performance, skills divide, awareness, information security and transaction security. Research limitations/implications: – Yet to be addressed, three criteria deemed as significant factors are recommended to be included in the model, namely, government readiness, system quality (usability, service quality and information quality) for supply side and social divide for demand side. These three criteria can help in proposing a successful G2C evaluation model. Additionally, the quantitative data used in this study were collected through paper-based questionnaires. Data collection through Internet can help to get responses from various parts of the country for future evaluation of G2C services. Practical implications: – The key findings of this study are vitally important for e-government strategies and policy makers to design and disseminate appropriate e-government services to Afghan citizens. The proposed evaluation model can also be used as a guideline for e-government development in Afghanistan. Originality/value: – A conceptual model for e-government services evaluation approach is proposed based on literature review. The proposed G2C evaluation model identifies and validates key factors and criteria in the context of Afghanistan.